2018
DOI: 10.1007/s00520-018-4375-y
|View full text |Cite
|
Sign up to set email alerts
|

Hispanic breast cancer patients’ symptom experience and patient-physician communication during chemotherapy

Abstract: The findings of this study underscore the need to improve patient-physician communication during chemotherapy to reduce the symptom burden among Hispanic breast cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 37 publications
1
17
0
1
Order By: Relevance
“…Konfliktursachen wie bspw. sprachliche Verständigungsprobleme, Behandlungszeiten oder die Ungewissheit der Patient/innen, was nach der Diagnose oder Behandlung auf sie zukommt, sind häufige Barrieren für die Kommunikation der Symptome und erschweren die Identifizierung von Problemen und die Behandlung [12,13]. Barrieren aufgrund der Kommunikation sind ein noch immer zentrales und ungelöstes Thema innerhalb der Versorgung [14].…”
Section: Hintergrundunclassified
“…Konfliktursachen wie bspw. sprachliche Verständigungsprobleme, Behandlungszeiten oder die Ungewissheit der Patient/innen, was nach der Diagnose oder Behandlung auf sie zukommt, sind häufige Barrieren für die Kommunikation der Symptome und erschweren die Identifizierung von Problemen und die Behandlung [12,13]. Barrieren aufgrund der Kommunikation sind ein noch immer zentrales und ungelöstes Thema innerhalb der Versorgung [14].…”
Section: Hintergrundunclassified
“…Disproportional cancer care resources, geographic distance, and structural barriers delay or impede their seeking timely cancer care [ 16 , 17 ]. Earlier studies have found that Spanish speaking BC Latina patients were less likely to receive cancer follow-up care, were more depressed, and in need of clinical information (i.e., side effects) as compared to English speaking BC patients [ 9 , 18 ], yet they did not report their psychological issues [ 19 ]. While these studies document problems in cancer care among Latinas, little is known about survivorship care issues, particularly regarding concerns and needs for survivorship care among rural Latina BC patients living in the US-Mexico border region.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the EHR has become a permanent feature of most medical offices. Patients may regard providers' divided attention and limited time to be necessities of modern healthcare, but these features of medical visits may make patients reluct to seek clarification or ask questions out of a sense of obligation to be undemanding on their provider (Antoun et al, 2019;Henselmans, Heijmans, Rademakers, & van Dulmen, 2014;Krok-Schoen et al, 2019;Schildmeijer, Nilsen, Ericsson, Brostom, & Skagerstrom, 2018;Wen & Gustafson, 2004). In the face of these challenges, the PCCMC offers a unified guide for developing communication training interventions, outlining a distinct set of patient-centered care strategies that providers can employ to bolster rapport, facilitate information exchange, and encourage patients to participate in shared decision-making.…”
Section: Implications For Empirical Research and Clinical Practicementioning
confidence: 99%